Survey on pathogenic Escherichia coli and Salmonella spp. in captive cockatiels (Nymphicus hollandicus) - Pontes, Patricia Silveira de (Braz J Microbiol, 2018)
We surveyed healthy captive cockatiels (Nymphicus hollandicus) for Escherichia coli and Salmonella spp. Cloacal swabs were collected from 94 cockatiels kept in commercial breeders, private residencies and pet shops in the cities of São Paulo/SP and Niterói/RJ (Brazil). Three strains of E. coli from each individual were tested for the presence of ExPEC-, APEC- and DEC-related genes. We evaluated the bla(TEM), bla(SHV), bla(OXA), bla(CMY), bla(CTX-M), tetA, tetB, aadA, aphA, strAB, sul1, sul2, sul3, qnrA, qnrD, qnrB, qnrS, oqxAB, aac (6)′-Ib-cr, qepA resistance genes and markers for plasmid incompatibility groups. Salmonella spp. was not detected. E. coli was isolated in 10% of the animals (9/94). Four APEC genes (ironN, ompT, iss and hlyF) were detected in two strains (2/27–7%), and iss (1/27–4%) in one isolate. The highest resistance rates were observed with amoxicillin (22/27–82%), ampicillin (21/27–79%), streptomycin (18/27–67%), tetracycline (11/27–41%). Multiresistance was verified in 59% (16/27) of the isolates. We detected strAB, bla(TEM), tetA, tetB, aadA, aphaA, sul1, sul2, sul3 resistance genes and plasmid Inc groups in 20 (74%) of the strains. E. coli isolated from these cockatiels are of epidemiological importance, since these pets could transmit pathogenic and multiresistant microorganisms to humans and other animals.